Nantucket blue - Howland, Leila (New York, N.Y. : Hyperion, 2013)
Seventeen-year-old Cricket Thompson is planning on spending a romantic summer on Nantucket Island near her long time crush, Jay--but the death of her best friend's mother, and her own sudden intense attraction to her friend's brother Zach are making this summer complicated.
Keywords: Dating (Social customs) -- Juvenile fiction; Interpersonal relations in adolescence -- Juvenile fiction; Best friends -- Juvenile fiction; Children of divorced parents -- Juvenile fiction; Grief -- Juvenile fiction; Dating (Social customs) -- Fiction; Interpersonal relations -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Divorce -- Fiction; Grief -- Fiction; Nantucket Island (Mass.) -- Juvenile fiction; Nantucket Island (Mass.) -- Fiction